Monoprophylaxis With Cephalosporins for Transrectal Prostate Biopsy After the Fluoroquinolone-Era: A Multi-Institutional Comparison of Severe Infectious Complications - Wenzel, Mike; von Hardenberg, Jost; Welte, Maria N.; Doryumu, Samuel; Hoeh, Benedikt; Wittler, Clarissa; Höfner, Thomas; Kriegmair, Maximilian C.; Michel, Maurice S.; Chun, Felix KH.; Herrmann, Jonas; Mandel, Philipp; et al. (Frontiers in Oncology, 2021)
Background: To compare infectious complication rates after transrectal prostate biopsies between cephalosporins and fluoroquinolones for antibiotic monoprophylaxis. Material and Methods: In the multi-institutional cohort, between November 2014 and July 2020 patients received either cefotaxime (single dose intravenously), cefpodoxime (multiple doses orally) or fluoroquinolones (multiple-doses orally or single dose intravenously) for transrectal prostate biopsy prophylaxis. Data were prospectively acquired and retrospectively analyzed. Infectious complications were evaluated within 30 days after biopsy. Logistic regression models predicted biopsy-related infectious complications according to antibiotic prophylaxis, application type and patient- and procedure-related risk factors. Results: Of 793 patients, 132 (16.6%) received a single dose of intravenous cefotaxime and were compared to 119 (15%) who received multiple doses of oral cefpodoxime and 542 (68.3%) who received fluoroquinolones as monoprophylaxis. The overall incidence of infectious complications was 1.0% (n=8). No significant differences were observed between the three compared groups (0.8% vs. 0.8% vs. 1.1%, p=0.9). The overall rate of urosepsis was 0.3% and did not significantly differ between the three compared groups as well. Both the application type (intravenous single dose vs. oral multiple doses) and the monotherapy of cephalosporins (vs. fluoroquinolones) were not associated with higher infection rates in multivariable logistic regressions after adjustment for patient- and biopsy characteristics (both p=0.7). Conclusion: Monoprophylaxis with third generation cephalosporins was efficient in preventing infectious complications after prostate biopsy. Single intravenous dose of cefotaxime and multiday regimen of oral cefpodoxime showed a low incidence of infectious complications <1%. No differences were observed in comparison to fluoroquinolones.